2021
DOI: 10.1063/5.0055565
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the contact time of droplet impact on superhydrophobic surface with protrusions

Abstract: Previous studies have pointed out that adding a single protrusion on the superhydrophobic surface can effectively reduce the contact time of droplets, which is of practical importance in applications like anti-icing, self-cleaning, and anti-frost. However, the droplet impact dynamics and the mechanism for contact time reduction are still far from completely understood. Therefore, in this paper, via a three-dimensional pseudopotential lattice Boltzmann model coupled with a modified curved boundary scheme (which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…33 Mazloomi Moqaddam et al for the first time realized accurate three-dimensional simulations involving realistic macrotextured surfaces and demonstrated that the reduction in contact time occurs entirely as a result of the increase in the droplet surface area which acts as storage for kinetic energy during the impacting process. 56,57 Shen et al studied a limited contact time of a bouncing droplet on a rationally designed TiO 2 nanowire-decorated Ti6Al4 V substrate (i.e., three-forked and cross-shaped macro-textures) and achieved contact times of 5.8 and 5.6 ms on the corresponding SHSs, which is very close to the theoretically calculated time (5.5 ms). 45 Gauthier et al illustrated that the contact time of drops impacting a nickel-wire-based macrotexture exhibits discrete values when varying the impact speed.…”
Section: Substratesupporting
confidence: 60%
See 1 more Smart Citation
“…33 Mazloomi Moqaddam et al for the first time realized accurate three-dimensional simulations involving realistic macrotextured surfaces and demonstrated that the reduction in contact time occurs entirely as a result of the increase in the droplet surface area which acts as storage for kinetic energy during the impacting process. 56,57 Shen et al studied a limited contact time of a bouncing droplet on a rationally designed TiO 2 nanowire-decorated Ti6Al4 V substrate (i.e., three-forked and cross-shaped macro-textures) and achieved contact times of 5.8 and 5.6 ms on the corresponding SHSs, which is very close to the theoretically calculated time (5.5 ms). 45 Gauthier et al illustrated that the contact time of drops impacting a nickel-wire-based macrotexture exhibits discrete values when varying the impact speed.…”
Section: Substratesupporting
confidence: 60%
“…Guo et al experimentally investigated the droplet impact dynamics on submillimeter-sized (or millimeter-sized) cross-scale cylindrical ridges of Cu/CuO-based SHSs, and the maximum reduction in contact time can be realized when the ridge diameter is close to that of the droplets . Mazloomi Moqaddam et al for the first time realized accurate three-dimensional simulations involving realistic macrotextured surfaces and demonstrated that the reduction in contact time occurs entirely as a result of the increase in the droplet surface area which acts as storage for kinetic energy during the impacting process. , Shen et al studied a limited contact time of a bouncing droplet on a rationally designed TiO 2 nanowire-decorated Ti6Al4 V substrate (i.e., three-forked and cross-shaped macro-textures) and achieved contact times of 5.8 and 5.6 ms on the corresponding SHSs, which is very close to the theoretically calculated time (5.5 ms) . Gauthier et al.…”
Section: Enhanced Water Repellency On Elastic Substratementioning
confidence: 99%
“…It was found that liquid possessed a faster retraction along the ridge than that on the flat surface, leading to a 37% reduction in contact time. 21 Following this work, studies focused on contact time reduction by asymmetric dynamics have been carried out, including the inclined surface, 22,23 curved surface, [24][25][26][27][28][29][30] surfaces with macro structures of different geometries, [31][32][33][34][35][36][37][38][39][40] moving surfaces, 41,42 and off-center impact. 43,44 Besides the aforementioned asymmetric approaches, symmetric bouncing by involving the droplet center to retraction with point-like structure to reduce contact time has also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…For a droplet with low viscosity, the impact velocity and the cylinder size, represented by the Weber numbers ( We = 2ρ R 0 u 0 2 /σ, with u 0 referring to the initial velocity of the droplet) and the size ratio of the cylinder to the droplet ( R * = R cy / R 0 , where R cy refers to the cylinder radius), respectively, are two key factors affecting the dynamic behaviors of the droplet. For example, as We increases or R * decreases, the uneven distribution of the momentum becomes more pronounced, leading to a continuous reduction in contact time. ,, This feature is distinct from the constant value observed on smooth horizontal surfaces (τ c ≈ 2.6), or the discrete forms on flat substrates patterned with single-ridge (exhibiting a reduction rate of 25 and 50%) or submillimeter-scale posts (showing a reduction rate up to 80%) . In an extreme case where a much higher We is applied or R * is much smaller, the droplet will directly break into smaller fragments, splash from the cylinder, or pass through the cylinder and fall off the surface, undergoing almost no retraction process. , When disregarding the aforementioned particular situations, considerable efforts have been made to correlate the contact time with the given conditions.…”
Section: Introductionmentioning
confidence: 92%